The emerging livestock feed markets in East Africa: A solution to feed shortages? - Nangole, E.; Lukuyu, Ben A.; Franzel, Steven; Baltenweck, Isabelle (International Livestock Research Institute, 2011)
Availability and access to feed resources is an important constraint to livestock productivity in East Africa. This study examined the production and marketing of livestock feeds in Kenya. The existing fodder value chains their constraints and opportunities are examined. A rapid appraisal survey was conducted with 93 actors along the value chain in November 2010. Findings showed that fodder marketing takes place at village and district levels. Trading at village level involved input sellers, producers who sold directly to rural retailers, rural consumers, or if they were near major district towns, to wholesalers. District level trading involved traders who sourced for fodder outside the district and retailed to wholesalers in major consumer markets within districts and to a lesser extend retailed in local areas. Service providers such as transporters and feed processors operated at all levels. Input providers comprised of agrovet and general retail shops while producers and consumers were mainly small and large scale farmers. Traders comprised of individual traders and cooperative societies. There are seasonal price variations and trading is common in the dry season. Fodder producers grow fodder for own use but sold excess often in the wet season. Few producers without livestock grow fodder for sale. Commonly traded feeds are Rhodes grass, maize stovers, oat straws and Lucerne hay and were preferred because they keep longer. Other forages are Napier grass and harvested roadside grass. Actors operated in uncoordinated manner. Cooperative societies played a key role in linking buyers and sellers, stimulating demand and providing credit. Input capital is perceived as a major constraint. Findings showed a need to promote feed marketing alongside feed conservation and feed processing as well creating platforms for linkages amongst actors. Market information is needed to enhance feed marketing systems.